Transformational Leadership of Madrasah Principals in Improving the Islamic-Based Pedagogical Competence of Teachers - Masruroh, Maghfirotul; Wahyudi, Wahyudi; Wizan, Kayno (QUALITY, 2026)
This study analyzes the transformational leadership strategies employed by the madrasah principalat MIT Nurul Islam Ngaliyan,in Semarang City to enhance teachers' pedagogical competence based on Islamic values.A qualitative case study design was adopted for this research. Data were collected through in-depth interviews, observations, and document analyses using purposive sampling; the principal served as the key informant. The findings reveal that the principal integrates four prophetic attributesShiddiq (truthfulness), Amanah (trustworthiness), Tabligh (conveying the message), and Fathanah (wisdom/intelligence)into three management dimensions: planning, implementation, and evaluation. During the planning stage, the integration of prophetic values achieved through the principal's personal example and by strengthening teachers' spiritualitythrough guidanceon Quranic recitation and memorization targets. During implementation, this integration is achieved through professional development programs and continuous mentoring, including comparative studies and curriculum training. In the evaluation stage, the integration is achieved through a tiered assessment model that prioritizes behavioral role modeling as the primary criterion. This strategy has proven effective in enhancing both teacher pedagogical competence and student achievement. Approximately 140 young students successfully memorized Juz 30 and the school secured second place in a district-level Siaga (Scout) skills competition involving 43 educational institutions. However, implementing this strategy also encountered internal resistance from some teachers and confusion about adopting instructional innovations. This study contributes to the development of a holistic Prophetic transformational leadership model for Islamic educational institutions.